Adaptive Access Control System - Amorim, Natalia de (2019)
Technology has provided efficiency and practicality for daily routines of people and companies. The market has solutions to flexibilize access that usually uses hard security controls which needs constant actions from a manager. This way, the paper aims to formalize a control access model that uses artificial intelligence techniques to adapt itself to the users behavior changes. Still, we present a case study of the implementation of this model. It was verified that the model presented satisfactory performance and it is suggested, as future works, the use of neural networks to make a comparison with this work.